Motor improvement of remote programming in patients with Parkinson's disease after deep brain stimulation: a 1-year follow-up - Wan, Xiaonan; Duan, Chengcheng; Lin, Zhengyu; Zeng, Zhitong; Zhang, Chencheng; Li, Dianyou (Frontiers in Neurology, 2024)
Background: Remote programming (RP) is an emerging technology that enables adjustment of implantable pulse generators (IPG) via the internet for Patients with Parkinson's disease (PwPD) who have undergone deep brain stimulation (DBS). Previous studies have not comprehensively explored the effectiveness of RP in managing motor symptoms, often omitting assessments such as the rigidity and retropulsion test during the follow-up. This study evaluates the comprehensive motor improvements and potential cost benefits of RP for PwPD with DBS.Methods: A retrospective analysis was conducted on two groups of patients-those who underwent RP and those who received standard programming (SP). Clinical outcomes including motor improvement, quality of life, and daily levodopa dosage, were compared between the groups at a 12 (± 3) month during in-clinic follow-up.Results: Forty-four patients were included in the study,18 in the RP group and 26 in the SP group. No significant differences were found in the frequency of programming sessions or clinical outcomes between the groups (p > 0.05). However, the RP group experienced significantly lower costs per programming session than the SP group (p < 0.05), despite living further from our center (p < 0.05).Conclusions: Our findings suggest that RP could significantly reduce the costs of programming for PwPD with DBS, without compromising the effectiveness of treatment across all motor symptoms in the short term.